2020
DOI: 10.1055/a-1096-1266
|View full text |Cite
|
Sign up to set email alerts
|

Blonanserin patch vs. Other Antipsychotics for Acute Schizophrenia: A Systematic Review of Double-blind, Randomized, Placebo-controlled, Phase 3 Trials in Japan

Abstract: Introduction The use of the blonanserin patch (BLO-P) for schizophrenia treatment was approved in Japan in 2019. This systematic review of trials in Japan assessed the efficacy and safety profile of BLO-P compared with other antipsychotics. Methods The systematic review included 6-week, double-blind, randomized, placebo-controlled, phase 3 trials in Japan that included patients with acute schizophrenia. Pooled data for patients receiving BLO-P 40 and 80 mg/day (BLO-P40+80) were compared with pooled data for pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Another reasons might be that the placebo response of LUR's DBRPCP3Ts was large compared with those of other antipsychotic's DBRPCP3Ts. 16 Although there was no significant difference in the primary outcome between LUR40 and LUR80, the effect size of LUR40 seems to be larger than that of LUR80. Dose-response meta-analysis of antipsychotic drugs for acute schizophrenia showed that the 95% effective dose of lurasidone was 147 mg/d.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Another reasons might be that the placebo response of LUR's DBRPCP3Ts was large compared with those of other antipsychotic's DBRPCP3Ts. 16 Although there was no significant difference in the primary outcome between LUR40 and LUR80, the effect size of LUR40 seems to be larger than that of LUR80. Dose-response meta-analysis of antipsychotic drugs for acute schizophrenia showed that the 95% effective dose of lurasidone was 147 mg/d.…”
Section: Discussionmentioning
confidence: 83%
“…The failure of these two DBRPCP3Ts 1,2 might be due to a type II error (ie, low statistical power). Another reasons might be that the placebo response of LUR’s DBRPCP3Ts was large compared with those of other antipsychotic's DBRPCP3Ts 16 . Although there was no significant difference in the primary outcome between LUR40 and LUR80, the effect size of LUR40 seems to be larger than that of LUR80.…”
Section: Discussionmentioning
confidence: 92%
“…The efficacy of the BTP (both 40 and 80 mg) is significantly superior to that of a placebo, improving positive and negative syndrome scale scores like other medications such as asenapine, brexpiprazole, and paliperidone extended release. 7 The BTP is associated with risks, including more severe extrapyramidal symptoms, compared with a placebo. However, the risk of weight gain with the BTP is lowest among these drugs.…”
Section: A Case Studymentioning
confidence: 99%
“…The BTP was the first patch-type drug in the psychiatric field and has been used in clinical practice since 2019. The efficacy of the BTP (both 40 and 80 mg) is significantly superior to that of a placebo, improving positive and negative syndrome scale scores like other medications such as asenapine, brexpiprazole, and paliperidone extended release 7 . The BTP is associated with risks, including more severe extrapyramidal symptoms, compared with a placebo.…”
mentioning
confidence: 98%
See 1 more Smart Citation